Good-Practice Non-Radioactive Assays of Inorganic Pyrophosphatase Activities - Baykov Alexander A; Anashkin Viktor A; Malinen Anssi M (MDPI, 2022)
Inorganic pyrophosphatase (PPase) is a ubiquitous enzyme that converts pyrophosphate (PPi) to phosphate and, in this way, controls numerous biosynthetic reactions that produce PPi as a byproduct. PPase activity is generally assayed by measuring the product of the hydrolysis reaction, phosphate. This reaction is reversible, allowing PPi synthesis measurements and making PPase an excellent model enzyme for the study of phosphoanhydride bond formation. Here we summarize our long-time experience in measuring PPase activity and overview three types of the assay that are found most useful for (a) low-substrate continuous monitoring of PPi hydrolysis, (b) continuous and fixed-time measurements of PPi synthesis, and (c) high-throughput procedure for screening purposes. The assays are based on the color reactions between phosphomolybdic acid and triphenylmethane dyes or use a coupled ATP sulfurylase/luciferase enzyme assay. We also provide procedures to estimate initial velocity from the product formation curve and calculate the assay medium's composition, whose components are involved in multiple equilibria.